MEDIA MIX MODELING COMPARISON OF INTERACTION MODEL TO SIMPLE LOG-LINEAR MODEL - Sharma, Priyanka; Meena, M Janaki; Ibrahim, S P Syed (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The objective of current study is to compare a new model for media mix problem with popular model named as simple log linear model. A modified approach proposed to improve the results of media mix model from simple log linear method includes the simultaneous effect of different media variables on sales. The combined effect caused by various media variables shows a synergy in the curve for sales and hence considering it makes the model much effective and accurate.